Menganalisis Bentuk dan Fungsi Verba dalam Cerita Rakyat “Si Buyung Besar” - Simaremare , Juni Agus; Siregar, Rumada; Silalahi, Laura; Nahampun, Rinaldi (Asosiasi dosen IDEBAHASA KEPRI, 2023)
The aim of this research is to describe the form and function of verbs in the folktale